What makes users willing or hesitant to use Fintech?: the moderating effect of user type. Issue 3 (9th April 2018) - Ryu, Hyun-Sun
Abstract : Purpose: The purpose of this paper is to better understand why people are willing or hesitant to use Financial technology (Fintech) as well as to determine whether the effect of perceived benefits and risks of continuance intention differs depending on user types. Design/methodology/approach: Original data were collected via a survey of 243 participants with Fintech usage experience. The partial least squares method was used to test the proposed model. Findings: The results reveal that legal risk had the most negative effect on the Fintech continuance intention, while convenience had the strongest positive effect. Differences in specific benefit and risk impacts are found between early and late adopters. Originality/value: This empirical study contributes to the novel understanding of the benefit and risk factors affecting the Fintech continuance intention.